Emotional labor and emotional intelligence on job performance: comparison of public and private organizations in China - Ma, S.; Silva, M. G.; Trigo, V.; Callan, V. (Global encyclopedia of public administration, public policy, and governance, 2020)
Emotional labor involves the management of feelings to create publicly observable expressions that are in accordance with the display rules established by organizations (Hochschild 1983). The display rules that shape the expression of such emotional labor are associated with occupational norms and organizational contexts (Grandey and Melloy 2017). Thus, due to the difference in management approaches, culture, and norms, emotional labor may differ in public and private organizations. Accordingly, emotional labor may impact upon job performance in public and private organizations, but this relationship is subject to emotional intelligence available (Newton et al. 2016). Specifically, this paper discusses differences in emotional labor among managers and professionals working in Chinese public organizations (CPOs), foreign-invested enterprises (FIEs), and Chinese privately owned enterprises (POEs), as well as differences in the relationships among emotional labor, emotional intelligence, and job performance.